2013
DOI: 10.1159/000352066
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Imaging of <b><i>Sarcoptes scabiei</i></b> Infestation Using Optical Coherence Tomography

Abstract: Background:Sarcoptes scabiei can be visualized with different imaging tools. Optical coherence tomography (OCT) may have the potential to describe the changes in skin morphology due to scabies infestation and visualize the parasite. Methods: Five patients from the Departments of Dermatology, Augsburg, Germany, and Roskilde, Denmark, were OCT scanned (VivoSight®; Michelson Diagnostics Ltd., UK). Mites were identified by epiluminescence and light microscopy to confirm the diagnosis. Results: OCT identified S. sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 13 publications
0
17
0
2
Order By: Relevance
“…Recently, a study of five patients has suggested that OCT may achieve a correct and straightforward diagnosis of scabies in vivo due to its ability to spot the mite both vertically and horizontally [ 52 ]. It clearly shows the burrows, allows visualizing the mites, and provides an estimation of their size.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a study of five patients has suggested that OCT may achieve a correct and straightforward diagnosis of scabies in vivo due to its ability to spot the mite both vertically and horizontally [ 52 ]. It clearly shows the burrows, allows visualizing the mites, and provides an estimation of their size.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…It clearly shows the burrows, allows visualizing the mites, and provides an estimation of their size. In the vertical images, the mite shows up as an ovoid, sharply marginated mass (mango/almond-shaped) of about 0.2 x 0.3 mm located just beneath the stratum corneum [ 52 ]. Its optical density is similar to that of the surrounding skin; however, a hyporeflective and a hyperreflective fringe, respectively corresponding to the burrow and to its scaly wall, are easily appreciable.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…5.2). Previous reviews of OCT focused on advanced screening in the fields of primary care, 53 microscopy, 54 rapid tissue screening, 55 phantoms, 56 high speed, 57 and translational research, 58 while recent application-specific OCT reviews covered ophthalmology, [59][60][61] cardiology, [62][63][64][65][66] dermatology, [67][68][69][70] novel applications in pulmonary medicine, 71 cancer, 72 and optical coherence elastography, 73 as well as OCT post-and signal processing. 74,75 This review focuses on high-speed technology (SS light technology and parallelization of OCT detection), label-free angiography, and multimodal OCT.…”
Section: Introductionmentioning
confidence: 99%
“…105 The same phenomenon can be observed in differentiating SSSS and TEN, where a SSSS demonstrates a split higher in the epidermis, and TEN shows a split at the DEJ. 104 Parasitic infestations of the skin with scabies mites and larva migrans and the naturally occurring demodex mites have been demonstrated with OCT. [106][107][108] Both larva migrans and scabies mites created subcorneal burrows, though only the scabies mite was visualized with OCT. 106,107 Demodex mites are situated corresponding to hair follicles and their degree of presence can be demonstrated with HD-OCT enabling treatment monitoring in demodexrelated diseases. 108 As mentioned earlier, the nail plate, nail fold, and nail matrix are visualizable with OCT, and various nail involving diseases have been investigated with OCT. [109][110][111] Onychomycosis can be seen as highly scattering elongated structures in the nail plate, 110 though showing a high rate of false positives compared to polymerase chain reaction, fungal cultures, and confocal scanning laser microscopy.…”
Section: Other Diseasesmentioning
confidence: 99%